Distinctive Feature of Thermally Grown Ultra Thin Silicon Nitride Film - Bahari, A.; Roodbari M. Atyabi, M.; Morgen, P. (Asian Journal of Chemistry, 2010)
In the current complementary metal oxide semiconductor (CMOS)- CPU generation the silicon gate oxide is 1.2 nm thick. A shrinking of this thickness with one atomic layer for the next generation will lead to a couple of orders of magnitude increase in tunneling current. Another critical issue for future generations is gate oxide degradation due to boron penetration into the oxide from the poly-silicon gate electrode. Ultrathin silicon nitride films have been identified as potential candidates to replace conventional silicon oxide gate dielectrics in current and future complementary metal oxide semiconductor, or as barrier layers between other high-dielectric constant materials and the silicon substrate. We have demonstrated a number of new processes to grow ultra thin silicon oxides and silicon nitrides based on the self limiting nature of the direct interaction between oxygen gas and heated silicon surfaces, or between atomic nitrogen produced in a microwave discharge and heated silicon surfaces. Theses pure ultrathin silicon oxide and nitride films have been studied on Si(100) in ultrahigh vacuum and studied by XPS and high resolution surface sensitive photoemission spectroscopy.